Development of Nutritionally Rich Orange- Fleshed Sweet Potato Lines: A Way to Increase Consumer Acceptance in Andhra Pradesh - Ashok, P; George, James; Priyanka, A Pavani (JOURNAL OF ROOT CROPS, 2017)
Sweet potato is a staple food in several tropical countries. It is one of the world’s highest yielding crops with the total production per unit area exceeding that of rice. Traditionally, sweet potato varieties produced and sold in Andhra Pradesh, have a pale and white coloured flesh, but new biofortified orange flesh sweet potato varieties (OFSP) have been introduced that contain high concentrations of β - carotene (pro-vitamin A). However, these varieties reportedly possess lower percentage of total sugars and dry matter content. A breeding programme was undertaken at Horticultural research station, Dr. Y.S.R Horticultural university, venkatramannagudem from 2013 to 2015 to develop new orange-fleshed sweet potato lines with high percentage of total sugars and dry matter to meet the end-users preferences. Genotypes of white and orange-fleshed sweet potato lines collected from different places were evaluated for beta carotene and total sugars. Based on the flowering habit and compatibility, parents were selected for crossing. Variety ST14 (Female parent) found to be superior in beta carotene content (8.5 mg/100 g) where as Kalinga (Male parent) was rich in total sugars (6.4%). Crossing programme was conducted between these parents and seeds were collected from the dried capsules of ST-14. Out of 55 seedling progenies, 14 orange fleshed genotypes were identified. Among the 14 F 1 orange fleshed genotypes VRSP-1 (PASP1) was found to be superior in yield (40.7 t ha -1 ), β -carotene (6.3 mg /100 g) and total sugars (7.8 %).